2022
DOI: 10.1007/s12187-022-09943-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Socio-Economic Vulnerability in Child Malnutrition Between Migrants and Non-Migrants Children (12–59 Months) in India: Evidence from a Cross-Sectional Study

Abstract: India has witnessed increasing trends in internal migration over the last three decades. In India, migrant children are not a homogeneous group and their reasons for movement and vulnerabilities vary across socio-economic stratum. For some children, migration may open possibilities and is associated with expanding social and economic spheres, but for many others, it may bring serious risks. Therefore, the study has been carried out to understand socio-economic vulnerability in child nutrition with migration st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the study, Santas and Eryurt (2020) note that the health condition of the children of rural areas and those who have migrated from rural areas to urban areas is better than the health conditions of the local children of urban areas. The study by Mishra et al (2022) shows the prevalence of child nutritional indicators between migrants and non-migrant children across different background characteristics in India, 2015-16. The results showed that among the social groups, scheduled caste children had a high variation in underweight (34% vs. 41.6%) and stunting (36% vs. 46%) between migrants and non -migrants' children.…”
Section: Resultsmentioning
confidence: 99%
“…In the study, Santas and Eryurt (2020) note that the health condition of the children of rural areas and those who have migrated from rural areas to urban areas is better than the health conditions of the local children of urban areas. The study by Mishra et al (2022) shows the prevalence of child nutritional indicators between migrants and non-migrant children across different background characteristics in India, 2015-16. The results showed that among the social groups, scheduled caste children had a high variation in underweight (34% vs. 41.6%) and stunting (36% vs. 46%) between migrants and non -migrants' children.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing access to food at the household level and improving parenting patterns as well as involving the role of the family in cultivating a family eating culture that has elements of positive nutritional education passed down from generation to generation 7 , especially responsive feeding of children can prevent a decline in children's nutritional status and prevent stunting 8 . The condition of poor communities with poor sanitation is a factor that is currently an obstacle to nutritional interventions in the community 9 . In addition, inappropriate complementary feeding behavior by caregivers due to lack of nutrition, knowledge about optimal feeding practices, inadequate awareness adequate regarding the frequency of feeding, and the amount of food that should be given to the child 10 , which constitutes a balanced diet and cultural beliefs are modifiable factors that can contribute to a decrease in the nutritional status of the child 11 .…”
Section: Introductionmentioning
confidence: 99%